Batch and fixed bed adsorption study for removal of acid and reactive dyes from aqueous solution using modified kenaf core - Al-Mamouri, Maytham Kadhim Obaid (2017)
The extensive use of commercial activated carbon as an adsorbent for the purification of industrial effluent from textile industry is not economically feasible due its high operational cost. Therefore, this research has been undertaken to explore the potential of certain agro based residues to produce suitable adsorbent. In this research, evaluation of the removal of reactive orange16 (RO16) and acid red 114 (AR114) dyes from aqueous solution was studied in batch and fixed bed column system by using modified kenaf core fibre (MKCF), in which kenaf being one of the agricultural crops used as low-cost adsorbents instead of activated carbon. In this